AN ANALYSIS ON GENERIC STRUCTURE AND LANGUAGE FEATURES OF PROCEDURE TEXTS MADE BY SECOND YEAR STUDENTS OF SMA SEMEN GRESIK (RETAIN, 2015)
Abstract English is an international language that has to be mastered in order to be able to face the development of new era nowadays. English, especially in educational aspect, has the significant impact for students. It is demanded for students not only being able to speak, but also to write. In some cases, the students who are learning English as a foreign Language faces a difficulty in writing an English text. Procedure text is one of several text types which are introduced to the Senior High School students in the second semester of the second year. The generic structures of this text are; title (goal), materials/equipment, and steps. The language features of the procedure text are imperative sentences, action verbs, connectives, adverbials, and simple present tense. Meanwhile, the procedure text is considered as the simplest text among the other text types, but there are still many students who get difficulty in organizing this text. Considering that phenomena, the writer is interested to conduct this analysis study which has two research questions. First, how is the second year of senior high school students’ knowledge of generic structures in their writing procedure texts?. Second, how is the second year of senior high school students’ knowledge of language features in their writing procedure texts?. The research design of this study is text analysis design. This study concerns on procedure text compositions, which are written by the second year students at the second semester in XI IPA 3 class of Sekolah Menengah Atas ( SMA ) Semen Gresik. The writer describes and analyzes the data in the form of words or sentences. The result of this study is not the representative of the students’ real ability in writing procedure text, since the text was written in a group. The result of data analysis indicated that most of the eleventh grade students of SMA Semen Gresik were able to apply the generic structure of procedure texts, in this case: title (goal), materials/equipment, and steps. It was found that some groups made several errors in arranging “materials” and “steps” parts of generic structure but some other groups arranged a good generic structure with some minor errors. The finding also showed that most of the students still did not pay attention to the importance of their text’s language features. There were several groups that did not use complete components of language features by missing the “connectives”. Furthermore, some groups were inconsistent in using simple present tense. They mixed some grammatical forms including passive and gerund in composing the text. Some groups did not apply “adverbials” in their text which was important to show the exact need for the materials or action. Thus, in conclusion, they were still confused and made several errors in applying the language features of procedure text. Key Words: Procedure Text, Generic Structure, Language Features. Abstrak Bahasa Inggris adalah bahasa internasional yang harus dikuasai agar mampu menghadapi perkembangan era baru saat ini. Bahasa Inggris, terutama dalam aspek pendidikan, memiliki dampak yang signifikan bagi siswa. Hal ini menuntut siswa untuk tidak hanya mampu berbicara, tetapi juga untuk menulis. Dalam beberapa kasus, siswa yang belajar bahasa Inggris sebagai Bahasa asing menghadapi kesulitan dalam menulis teks bahasa Inggris. Teks prosedur adalah salah satu dari beberapa jenis teks yang diperkenalkan kepada siswa SMA di semester kedua tahun kedua. Struktur generik teks ini adalah; title (tujuan), bahan/peralatan, dan langkah-langkah. Fitur bahasa dari teks prosedur adalah kalimat perintah, kata kerja, kata hubung, kata keterangan, dan present tense sederhana. Sementara itu, teks prosedur dianggap sebagai teks paling sederhana di antara jenis teks lain, tetapi masih banyak siswa yang mengalami kesulitan dalam menulis teks ini. Berkaca pada fenomena itu, penulis tertarik untuk melakukan studi analisis ini yang memiliki dua pertanyaan penelitian. Pertama, bagaimana pengetahuan siswa tahun kedua di SMA tentang struktur generik dalam teks prosedur tulisan mereka ?. Kedua, bagaimana pengetahuan siswa tahun kedua di SMA tentang fitur bahasa dalam teks prosedur tulisan mereka ?. Desain penelitian dalam studi ini adalah desain analisis teks. Studi ini terfokus pada komposisi teks prosedur yang ditulis oleh siswa tahun kedua di semester kedua di kelas XI IPA 3 Sekolah Menengah Atas (SMA) Semen Gresik. Penulis menggambarkan dan menganalisa data dalam bentuk kata-kata atau kalimat. Hasil penelitian ini bukan wakil dari kemampuan nyata siswa dalam teks prosedur tertulis, karena teks ditulis dalam kelompok. Hasil analisis data menunjukkan bahwa sebagian besar siswa kelas XI SMA Semen Gresik mampu menerapkan struktur generik dalam teks prosedur, dalam hal ini: Judul (tujuan), bahan / peralatan, dan langkah-langkah. Ditemukan bahwa beberapa kelompok membuat beberapa kesalahan dalam mengatur